Mencari Hukum yang Berkeadilan bagi Anak melalui Diversi - Rr. Putri A. Priamsari (Perspektif Hukum, 2018)
According to UNICEF, no less than 4000 Indonesian children are brought to court every year with reports of relatively minor crimes such as theft, persecution, spreading hoaxes and others. Where children who are faced with the law generally are not accompanied by legal counsel or social services. Indonesia has had a umbrella act in protecting children's welfare, namely Law Number 4 of 1979 concerning Child Welfare which was then followed by Law Number 23 of 2002 concerning Child Protection which has now been replaced with Law Number 35 of 2014 concerning Child Protection as implementation of the Convention on the Rights of the Child (Convention on the Rights of the Child, 1989, New York). Taking into account that the handling of child cases dealing with the law must really guarantee the protection of the best interests of the child and must aim at the creation of Restorative Justice, both for Children and Victims of Children and to create Restorative Justice, before resorting to judicial proceedings at the prosecution level General must strive for Diversion. Provisions regarding this diversion are also regulated in Supreme Court Regulation Number 4 of 2014 concerning Diversion. The enactment of the 2014 PERMA is intended so that juvenile justice in Indonesia can be carried out more efficiently, while still considering its welfare.